Cardiac pacemaker–related endocarditis complicated with pulmonary embolism: Case report - Šačić, Dalila; Petrović, Olga; Zamaklar-Trifunović, Danijela; Ivanović, Branislava (Frontiers in Cardiovascular Medicine, 2023)
Cardiac device–related endocarditis as a device-therapy complication is a growing problem due to higher life expectancy and the increasing number of abandoned leads and subclinical symptoms. We reported a case of a 47-year-old woman with an implanted pacemaker who was admitted to the clinic for cardiology due to the right-sided device-related infective endocarditis of the pacemaker leads with vegetations, predominantly in the right atrium and right ventricle and complicated by pulmonary embolism. Several years after pacemaker implantation, she was diagnosed with systemic lupus erythematosus and started immunosuppressive therapy. The patient was treated with prolonged intravenous antibiotic therapy. The atrial and ventricular lead was extirpated, and the posterior leaflet of the tricuspid valve was shaved.